Short notes on Saproxylic Arthropods of Batu Timbang research station, Imbak Canyon Conservation Area - Mahadimenakbar M. Dawood; Bakhtiar Effendi Yahya (Universiti Malaysia Sabah, 2019)
A sampling of saproxylic arthropods was conducted from a fallen log located close to an existing trail and was situated under shaded area. All arthropods (larvae, pupae and adults) found in the fallen log were collected and kept in vials containing 75 % ethanol solution for identification. A total of 7 insect orders and 1 class of arthropod (Diplopoda) were collected. 15 species of ants were collected but only 1 species observed residing in the fallen log. Other ants were collected foraging on the deadwood. Only one species of termites (Blattodea: Havilanditermes atripennis) was recorded. Other orders found include Coleoptera (beetles), Orthoptera (mole cricket), Dermaptera (earwig), Diptera (fly) and Lepidoptera (moth).